Answer:
(a) 0
(b) f(x) = g(x)
(c) See below.
Explanation:
Given rational function:
![f(x)=(x^2+2x+1)/(x^2-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/447p09431ub9d3bv88gif9mxiv0io94xx5.png)
Part (a)
Factor the numerator and denominator of the given rational function:
![\begin{aligned} \implies f(x) & = (x^2+2x+1)/(x^2-1) \\\\& = ((x+1)^2)/((x+1)(x-1))\\\\& = (x+1)/(x-1)\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/yj7fsbfudkabvpe4vdthbz8b543utw93uh.png)
Substitute x = -1 to find the limit:
![\displaystyle \lim_(x \to -1)f(x)=(-1+1)/(-1-1)=(0)/(-2)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/nx3cy5xkb473smww62p1l6sk54r9cy3f3u.png)
Therefore:
![\displaystyle \lim_(x \to -1)f(x)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/g94c40kjs7aux9rxq9jq8wrqlybgi68kvs.png)
Part (b)
From part (a), we can see that the simplified function f(x) is the same as the given function g(x). Therefore, f(x) = g(x).
Part (c)
As x = 1 is approached from the right side of 1, the numerator of the function is positive and approaches 2 whilst the denominator of the function is positive and gets smaller and smaller (approaching zero). Therefore, the quotient approaches infinity.
![\displaystyle \lim_(x \to 1^+) f(x)=(\to 2^+)/(\to 0^+)=\infty](https://img.qammunity.org/2023/formulas/mathematics/high-school/g8568k6dkfuaefphzjcjsbxawnobbrhcyc.png)